Effects of Gender on Leadership, Entrepreneurial Orientation and Organisational Performance - Arham, Ahmad Fadhly; Norizan, Nor Sabrena; Muslim, Nurliza Haslin; Aksan, Azwin (UiTM Press, 2020)
There are two streams of literature regarding relationship between gender and various organisational outcomes and variables affecting performance. Some scholars have found that there are significant differences between males and females regarding their leadership behaviours, entrepreneurial orientation and how organisations perform. Thus, the focus, development and assistance provided to male and female entrepreneurs are different. However, findings also indicated that there is no significant difference between genders. In this study, data were taken from 395 respondents representing either the owners or top managers of various SMEs organisations operating within the manufacturing and services sector in Malaysia. Within the context of SMEs in Malaysia, the result failed to recognise any significant differences between male and female respondents with regards to their leadership behaviours, entrepreneurial orientation and organisational performance. Male and female owners and top managers of SMEs in Malaysia were perceived to be the same in their leadership orientation, entrepreneurial approach and outcomes for organisations. The novelty of this research lies in its attempt to explore gender differences of leaders of SMEs in Malaysia.